PENENTUAN SUMBER GAS OKSIGEN UNTUK PERCOBAAN VOLUME MOLAR GAS - Rery, Usman (Jurnal Pilar Sains, 2008)
Based on the result of research have found that the better gas used in experiment the molarvolume of gas is oxygen than hydrogen or carbondioxide. From that research, the researcherwant to develop it into specific issue that “which the source of oxygen is better to determinethe molar volume of gas” to produce of the oxygen taht the molar volume resembled to themolar volume of ideal gas if measured at standard condition. Besides the problem mentinedabove, researcher also want to know how many substances are standard to use in theexperiment molar volume of gas and determine which instrument is better used from twodiffrent instruments, certainly a simple equipment, practical, easy to design and less ofmistakes in observation. So that the result will be accurate.Key Word : Determine, molar volume of gas